What Europe and the US could learn from the Covid Crisis - Aiginger, Karl (Archives of Business Research, 2021)
The European Economy is underperforming in the Covid Crisis, as it did in the Financial Crisis. If economic strength is measured by growth of GDP, Europe’s recovery in 2021 will be two percentage points below the loss in 2020, while the US will enjoy a net gain of 2 percentage points in these two crisis years. To the benefit of Europe, the paper finds that fatal causalities relative to population due to Covid were lower in Europe, and we therefore conclude that Europe chose a different tradeoff between economic and health goals. We report differences in fiscal and monetary response, but also in structural policy, governance and the political process in the two regions. Decisions in the US, once a problem has been recognized as important, are quicker; more resources can be shifted, even if the public debt is already very high. Finally, we screen performance for sustainability and life expectancy, which shows advantages for Europe that could be extended in the recovery programs.